IMPROVING BUSINESS MANAGEMENT EFFICIENCY THROUGH DIGITALIZATION ASSISTANCE USING SALES MASTER APPLICATION IN MSMES CANTEEN - Rita J D Atarwaman; Mutiara Nazliza; Rafly Aitya Saputra; Yulianti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Micro, Small, and Medium Enterprises (MSMEs), especially canteen businesses, play an important role in supporting local economic activities due to their high daily transaction intensity. However, many MSME canteens still face problems in transaction recording, inventory management, and sales reporting because these activities are carried out manually. This community service activity aims to improve business management efficiency through digitalization assistance using the Sales Master application. The methods used include initial surveys, digitalization socialization, application usage training, hands-on assistance, and evaluation. The results show that MSME actors experienced improvements in transaction recording accuracy, inventory control, and accessibility of sales reports. The implementation of the Sales Master application positively impacts operational efficiency and supports the independence of local MSMEs.